Copper monitoring in vineyard soils of the Tikvesh region, North Macedonia - Hristina Poposka; Dusko Mukaetov; Julijana Cvetkovic; Marjan Andreevski; Milena G. Tasevska; Katerina O.Bandjo; Dusko Nedelkovski; Roze M. Gjoljevska (University of Banjaluka, Faculty of Agriculture, 2022)
This research studies the copper contents in vineyard soils under vineyards affected by the long-term use of copper-based fungicides and evaluates the extent of this influence on the super accumulation in the main viniculture growing regions in North Macedonia. The soil samples were taken from individual vineyards located in the Tikvesh region, from two depths: 0-30 and 30-60 cm. At the same time, control samples were collected from each of the visited sites. The control samples were taken from untreated nearby locations under natural conditions in order to determine the background concentrations. The available copper (Cu) contents were analysed on soil samples taken from 100 locations, 50 of which represent vineyard soils (organic and conventional farming) and 50 control samples from nearby forests and sites. The main finding is that the average available copper concentrations are significantly higher in soils under vineyards, compared to the background concentration in control samples, especially in these with organic farming where the use of coper-based fungicides is more intensive. A comparison of the copper contents in vineyards to the background concentrations of control samples clearly confirmed the anthropogenic influence. A significantly very high level of copper (10.70-18.77 mg/kg) was measured in the soil samples from organic farming. The control samples contained a significantly lower concentration of copper, between average 1.39- 1.62 mg/kg (0-30 cm) and 0.68-0.88 mg/kg (30-60 cm). According to the micronutrient rating as related to a soil test with the DTPA extraction reagent (Jones, 2001) applied in this study, a significant potential ecological risk has been noticed in the agricultural soil samples (organic and conventional production).
Keywords: copper, soil, sample, vineyard, Tikvesh